International effort to create the International Journal of Environmental Resilience Research and Science (IJERRS) - EDITORIAL - Carniatto, Irene (International Journal of Environmental Resilience Research and Science, 2019)
We live in an odd moment in our society, when Planet Earth shows signs of exhaustion of its capacity to support Life. The term resilience has come to be well known, mainly through the media and scientific studies. Environmental resilience is a planetary condition that is sought and must be pursued through public policies and daily actions of each being that inhabits the Planet. It is with a focus on the need to advance resilience, that we present to the academic community, especially to researchers, managers and the community in general, a publication and a new communication channel - International Journal of Environmental Resilience Research and Science (IJERRS), whose first edition is the result of scientific research and relevant projects presented by the participants of an exciting workshop, where a channel was opened in which you will test ideas, together with policy makers, on the pressing issue of financing the development resilient to the rural and urban climate. Therefore, this magazine is one of the results of the WORKSHOP UNITED KINGDOM - BRAZIL on the "Financing of Urban Development Resilient to Climate", held from September 9 to 12, 2019 in Foz do Iguaçu - Paraná - Brazil. Also, during the Workshop, the International Research Network on Climate Resilient Development - RIPEDRC - Climate Resilience Network was launched, when the researchers, managers and companies present expressed their desire to continue working together to develop innovative projects mainly for the municipalities of the Triple Frontier: Foz do Iguaçu (BR), Cuidad del Este (PY) and Puerto Iguazu (AR), and contributing to the Internationalization of the graduate programs of the universities involved, which bring about an improvement in the quality of life, resilience, territorial intelligence and new ways of living, relating and being in the world. Thus, this journal is the result of this international group of the network that starts its activities with the participation of 75 researchers from 45 institutions in Brazil, the United Kingdom, Paraguay, Argentina, Chile, Guatemala, Bolivia, Spain, Italy and other countries that are in study for partnership.